“Ethereal Journeys” of a Wanderer in William Cowper and Yahya Kemal Beyatlı - Şafak Altunsoy (Selçuk Üniversitesi Edebiyat Fakültesi Dergisi)
This study investigates the heterotopic representations of home and evening in the selected poems of William Cowper and Yahya Kemal Beyatlı. The study starts with the discussion of William Cowper and Yahya Kemal Beyatlı as unique poets in their national literatures to consolidate their comparable qualities based on their personal lives and their poetic styles and to clarify such a choice for the comparative analysis of the poets. Then, the study elaborates on the significance of the recurrent images related to home and evening since the concept of ‘home’ serves as a powerful metaphor, representing the coexistence of opposite realms in the poetries of Cowper and Beyatlı. Similarly, the transitional moment of evening symbolises the gradual shift in the speakers’ perception as they navigate between different imaginary spaces through observation and imagination, which creates the idea of journey/ wandering and a constant desire for searching in the poems by the two poets. Besides adapting Foucault’s theory of space in “Of Other Spaces” for the comparative analysis of the poems, the study also suggests that the narrators of Cowper and Beyatlı find solace and a sense of renewal within the confines of their homes or the natural landscape providing a recuperative space with the affirming reminiscences. Hence, in Cowper’s long narrative poem, The Task (1785) and Beyatlı’s poems from Our Own Vault of Heaven, The Idea of Journey and Communion (1961) the image of a protected home catalyses the rational boundaries and language, enabling the speakers to cope with their recurring sorrows/ anxieties. The study concludes that an English pre-Romantic/ neo-classical poet and a Turkish neo-classical poet can poeticise similar contradictory feelings of joy and despondence in the natural phenomenon of evening and the comforting space of home.